DIVIDEND POLICY, LEVERAGE ON COMPANY VALUE AND TAX AVOIDANCE AS MODERATING VARIABLES - Heni Pujiastuti; Farid Subkhan; Irene Zepania (Dinasti Publisher, 2022)
This study aims to determine the effect of Dividend Policy (DPR) and Leverage (DER) on Firm Value (PBV) with Tax Avoidance (ETR) as a moderating variable. Sources of data in the form of secondary data include the annual financial statements of consumer goods manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period. Based on a sample of 14 companies, it was found that dividend policy and tax avoidance did not affect firm value, while leverage had an effect on firm value. Tax Avoidance Ability to moderate the Dividend and Leverage Policy on Company Value has a weak influence, this is because the company complies more with tax regulations than having to deal with the tax authorities.